HUBUNGAN ANTARA AKTIVITAS FISIK DAN INDEKS MASSA TUBUH (IMT) DENGAN KEJADIAN PRE-MENSTRUAL SYNDROME PADA REMAJA PUTRI - Isrowiyatun Daiyah; Ahmad Rizani; Eryna Rezki Adella (Sekolah Tinggi Pariwisata Mataram, 2021)
Premenstrual syndrome (PMS) is a set of physical and mental symptoms that occur one week to several days before menstruation and vanish until menstruation arrives. Premenstrual syndrome (PMS) is characterized by severe pain. While premenstrual syndrome is not life threatening, it can have a negative impact on a woman's mental health and productivity. Physical activity and Body Mass Index (BMI) are two factors that affect the occurrence of premenstrual syndrome. The aim of this research was to see if there was a connection between physical activity and body mass index (BMI), as well as the prevalence of premenstrual syndrome in young women. The approach used in this analysis was a literature review. Data was gathered from 10 relevant journals, 7 of which were national and 3 of which were foreign. Secondary data was used in the review, and data analysis was completed in September 2020. Both trials with the dependent variable premenstrual syndrome and associated physical activity as well as the independent variables body mass index (BMI) were included in this study. Journals and academic papers for this study were collected from an online database that was available from 2015 to 2020.